2021
DOI: 10.3390/w13243487
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Agricultural Areas on Spatio-Temporal Variability of Daily Minimum Extreme Flows during the Transitional Seasons (Spring and Fall) in Southern Quebec

Abstract: Several statistical methods were used to analyze the spatio-temporal variability of daily minimum extreme flows (DMEF) in 17 watersheds—divided into three homogenous hydroclimatic regions of southern Quebec—during the transitional seasons (spring and fall), during the 1930–2019 period. Regarding spatial variability, there was a clear difference between the south and north shores of the St. Lawrence River, south of 47° N. DMEF were lower in the more agricultural watersheds on the south shore during transitional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Destouni et al (2013) and Jaramillo et al (2013) linked historical agricultural development at the expense of grassland to increases in runoff and actual evapotranspiration in several watersheds in Sweden, thus reducing the available water for recharge. Meanwhile, increases in spring and fall minimum river flows in southern Quebec (Canada) were linked to a reduction in agriculture area in the 1950 s and were interpreted as an increase in GWR (Assani et al, 2021). Alternatively, Greenwood and Buttle (2018) showed that agricultural LC notably increased the depression‐focussed GWR compared with forested area in a complex and highly permeable moraine deposit in southern Ontario (Canada), mainly due to more intense winter soil frost, producing more snowmelt runoff that accumulated in highly permeable topographical depression, thus favouring GWR compared with agriculture area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Destouni et al (2013) and Jaramillo et al (2013) linked historical agricultural development at the expense of grassland to increases in runoff and actual evapotranspiration in several watersheds in Sweden, thus reducing the available water for recharge. Meanwhile, increases in spring and fall minimum river flows in southern Quebec (Canada) were linked to a reduction in agriculture area in the 1950 s and were interpreted as an increase in GWR (Assani et al, 2021). Alternatively, Greenwood and Buttle (2018) showed that agricultural LC notably increased the depression‐focussed GWR compared with forested area in a complex and highly permeable moraine deposit in southern Ontario (Canada), mainly due to more intense winter soil frost, producing more snowmelt runoff that accumulated in highly permeable topographical depression, thus favouring GWR compared with agriculture area.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that land use and LC had little impact on GWR simulation, or that land use and LC impacts were smaller than those of climate change (Guerrero‐Morales et al, 2020; Mohan et al, 2018; Morgan et al, 2021; Shuler et al, 2021). These differences are most likely due to the fact that it can be challenging to distinguish the impacts of climate change from the impacts of land use and LC changes on GWR, and on all components of the water budget more generally (Assani et al, 2021; Goodbrand et al, 2022; Young et al, 2019). The study scale could also determine the importance of the impacts of land use and LC changes on GWR simulations, as local impacts of changes are not necessarily visible at larger scales (Shuler et al, 2021; Zomlot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It follows that, despite the significant increase in rainfall, part of the excess water provided by this increase was absorbed by the soil in uncropped land and reforested land. This increase in infiltration following the reduction in agricultural areas has, moreover, resulted in a significant increase in minimum flows supplied by groundwater in the fall (e.g., Assani et al, 2021Assani et al, , 2022. This increase in minimum flows was not observed on the north shore despite greater surface area of wetlands.…”
Section: Analysis Of the Temporal Variability Of Fall Daily Maximum F...mentioning
confidence: 99%